2018
DOI: 10.3390/polym10070734
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Shear Behavior of High-Density Polyethylene Geomembrane Interfaces

Abstract: As a product of polymeric materials, geomembranes (GMs) are widely used in engineered systems as impervious barriers due to their low permeability. In this study, a large-scale composite shear test apparatus was developed to investigate the shear behaviors of various GM interfaces. A series of direct shear tests were conducted on GM–soil, GM–geotextile, and GM–concrete interfaces. Two types of high-density polyethylene (HDPE) GMs, a smooth GM and a textured GM, were used to evaluate the effect of GM-texturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The interface friction angles (uncured) were compared with the results obtained in the literature and are summarised in Table 5. In this study, the friction angles of the GM-soil interfaces were consistent with the results of Fleming et al [21], Frost et al [23], Cen et al [37], and Stark and Santoyo [50]. It was also evident that the friction angle of the coarse-grained soil was greater than that of the fine-grained soil.…”
Section: Comparison With the Interface Friction Angles In Literaturesupporting
confidence: 91%
See 2 more Smart Citations
“…The interface friction angles (uncured) were compared with the results obtained in the literature and are summarised in Table 5. In this study, the friction angles of the GM-soil interfaces were consistent with the results of Fleming et al [21], Frost et al [23], Cen et al [37], and Stark and Santoyo [50]. It was also evident that the friction angle of the coarse-grained soil was greater than that of the fine-grained soil.…”
Section: Comparison With the Interface Friction Angles In Literaturesupporting
confidence: 91%
“…The interface friction angles of the coarse and angular soils are higher, as listed in Table 4. It has been determined that soils with different morphological properties (roundness and sphericity) can affect the internal friction angle [23][24][34][35][36][37]. The internal friction angle increased as the particle size increased because larger particles required more friction force to roll and reach the sliding state after the lock was released at the peak [36,38,39].…”
Section: Traditional Direct Shear Testmentioning
confidence: 99%
See 1 more Smart Citation
“…TIWARI and SATYAM's [18] large-scale direct shear and unconfined compressive strength tests on the interaction at the interface between the subgrade, polypropylene fibers, triaxial geogrids, and biaxial geogrids revealed that the shear strength of the reinforced subgrade increased by 177% with the addition of bi/triaxial geogrids and polypropylene fibers. CEN et al [19] developed a large-scale composite shear test apparatus to study the shear behavior of various geomembrane interfaces, observing higher peak shear stresses and shear displacements on textured geomembrane-soil interfaces compared to smooth ones. ZHANG et al [20] conducted a series of direct shear tests to reveal the shear mechanism of the concrete-HDPE material interface, finding that the interface exhibited evident strain-softening behavior during shearing, with shear strength linearly increasing with normal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Adding reinforcement material to soil is internationally considered as an effective method to improve soil properties (i.e., strength performance, permeability behavior, and erosion resistance) [1,2,3,4,5,6]. In general, the reinforcement material is divided into two types, namely, physical reinforcement material and chemical additives.…”
Section: Introductionmentioning
confidence: 99%